Geo-hydrological and seismic risk awareness at school: Emergency preparedness and risk perception evaluation. (November 2019) - Bandecchi, Anna Elisa; Pazzi, Veronica; Morelli, Stefano; Valori, Luca; Casagli, Nicola
Abstract: One of the targets of the Sendai Framework is to reduce disaster damage to critical infrastructure and the disruption of basic services, particularly in educational facilities, and to develop their resilience. To assess the geo-hydrological and seismic risk awareness in schools in Tuscany (Italy), ad hoc questionnaires were set up. These questionnaires focused on the knowledge of the correct behaviours and procedures during an emergency as well as risk awareness and perception. These questionnaires were different for each school age (from 3 to 19 years old) and were even conceived as a didactic instrument. We distributed 5899 in total (820 to the school staff and 5079 to the students of each school stage), and the analysis shows that, a) as age and responsibilities increase, geo-hydrological and seismic risk awareness and preparation do not increase proportionally, which is almost inadequate for the staff, and b) there is a disconnect between the school evacuation plans and the city civil protection plan. The proposed questionnaires were found to be a good instrument for both disaster education (to increase and improve the level of awareness) and school-resilience evaluation (not only within the Geohazard Safety Classification method) to plan further action and improve it. Therefore, the present study suggests priorities for future school-based emergency management efforts, i.e., to increase school resilience and develop a resilience culture in the community. It is necessary to improve the dissemination of information on the local geo-hydrological and seismic hazards and ensure a link among the different emergency plans. Highlights: Ad hoc questionnaires to assess the current awareness degree. Questionnaires different for each school age conceived as didactic instrument. As result young children knowledge is perfectly adequate to their age. As result the awareness and preparation do not increase proportionally with the age. As result the hazard is usually underestimated.